Nucleophilic cross‐linked, dextran coated iron oxide nanoparticles as basis for molecular imaging: synthesis, characterization, visualization and comparison with previous product. (22nd April 2014) - Borny, Robert; Lechleitner, Thomas; Schmiedinger, Thomas; Hermann, Martin; Tessadri, Richard; Redhammer, Günther; Neumüller, Josef; Kerjaschki, Dontscho; Berzaczy, Gundula; Erman, Gürkan; Popovic, Martin; Lammer, Johannes; et al.
<x xml:space="preserve">Abstract</x> We present a new synthesis protocol for a multivalent, multimodality, nucleophilic nanoparticle ideal for in vivo imaging. Stability requirements necessitated covalent cross‐linking of the carbohydrate cage, easy functionalization the introduction of sterically accessible amine groups. The new protocol aimed at more uniform particle size, less clustering and superior magnetic properties compared with commercial nanoparticles. Particles were precipitated from Fe2+ and Fe3+ in the presence of 10 kDa dextran monodispersed from the aerosol phase. Cross‐linking was achieved with epichlorhydrin, nuclophilication with NH3, purification with ultrafiltration and dialysis. Particles and a commercial product (Rienso®, Takeda Pharma) underwent physicochemical characterizations. Biocompatibility was assessed by Resazurin on LLC‐PK1 cells; the internalization rate was measured for three cell lines (HAEC, HASMC, HT29). Core size was 5.61 ± 1.25 nm; hydrodynamic size was 49.56 ± 11.73 nm. The number of sterically accessible amine groups averaged 9.9. The cores showed cubic magnetite structure. Values of r1 and r2 were 10.9 and 148.17 mm−1 s−1. Cellular viability was unchanged after incubation. Introduction of aerosol phase dextran resulted in a reduction of the overall hydrodynamic diameter and a narrower size distribution of the synthesized particles. Electron tomography visualized for the first time the postulated 'hairy layer' of the dextran coating and enabled the measurement of the overall diameter of 100.2 ± 7.92 nm. The resulting nanoparticle is biocompatible, functionalizable and detectable at nanomolar concentrations with MRI and optical imaging. It can potentially serve as a platform for multimodal molecular imaging and targeted therapy approaches. Copyright © 2014 John Wiley & Sons, Ltd.